Los derechos económicos sociales y culturales en el texto de la Constitución y en la jurisprudencia del Tribunal Constitucional - Rubio, Patricio (2013)
This article deals with Cultural, Social and Economic Rights established in the Constitution and in Constitutional Case Law. So, after explaining its nature, state’s role according preservation and enforceability,relationship with other fundamental rights, among other key points, it isi ntended to answer, dealing with those rights, which of two scenarios have prevailed: internationalization of constitutional law or constitutionalization of international law.